Risco geotécnico: uma abordagem estocástica para análise da estabilidade de taludes da Barragem Olho d’Água no Estado do Ceará - Araújo, Franklim Rabelo de (2013)
The evolution of slope stability analysis in geotechnical engineering has followed closely the development of soil mechanics . Slope landslides are one of the most frequent forms of mass movement . In the case of earth dams, three difficulties are encountered when analyzing the slope stability: a) the variability of soil strength parameters, b) difficulty of predicting the conditions of water flow and resulting piezometric pressures, and c) difficulty in predicting the most probable forms of rupture, the potential surfaces associated to them, and the rupture mechanisms involved . These difficulties reflect directly on the number of failures recorded with dams, which accounts for 66 % of accidents in dams around the world. Data from the National Water Agency of Brazil show that between 2002 and 2010, 800 incidents were recorded dams. As major accidents, the rupture of tailings in Cataguazes dam in the state of Minas Gerais in March 2003, which left millions of people without water for weeks , due to leakage of caustic soda in the Paraíba do Sul river , as well as the failure in the Algodão Dam, in May 2009, in Piauí state in northeastern Brazil may be mentioned . Thus, because of the many uncertainties in the projects of dams, the use of a methodology that takes into account the variability of the components involved in the analysis of slope stability of dams is necessary, since these uncertainties are not considered in deterministic methods. The probabilistic analysis of slope stability using the Monte Carlo method, turns out to be an important evaluating tool during construction, filling and operation of earth dams. This work proposes a simplified methodology for estimating soil hydraulic parameters, by means of back-analysis of seepage conditions, comparing the pressure heads measured by standpipe piezometer in the dam, together with those calculated by commercial computing program to, then, estimate the dam slopes probability of failures. The reliability analysis of the downstream slope of the dam in the high level of water condition was done, such as the backslope stability analysis during rapid drawdown of the Olho d’Água dam in the State of Ceará, Brazil.